From a Uniform to a Multiform Understanding of Church. Foundations of Exchange in the Preconciliar Missiology of Jean Bruls - Ooms, Toon (Exchange, 2022)
During the first half of the 20th century, genuine exchange between the churches within Roman Catholicism was virtually non-existent. Church was conceived of as the one Roman Catholic Church, and the relationship between churches was one of a Western unilateralism. Shortly after the Second World War, the Belgian Catholic missiologist Jean Bruls (1911–1982), editor-in-chief of the missiological journal Église Vivante, pointed to the necessity of an exchange (“échange”) between the Western church and the non-Western churches. This article argues that Bruls’ early attention to interchurch exchange was the result of a new conceptualization of Church. The article shows to what extent Bruls’ missiology was an anticipation of the mission doctrine of the Second Vatican Council (1962–1965).